Simulation of Pollutant Gas Dispersion on Case Study of Lontar 3 Coal Fired Power Plant in Addition into 1 x 660 MW Capacity in Kemiri, Tangerang District, Banten Province - Eko Sugiharto; Taufik Abdillah Natsir; Abdul Rozaq (Universitas Gadjah Mada, 2014)
Air quality simulation has been performed for additional capacity of Banten 1 x 600 MW Coal Fired Power Plant toward air quality degradation in its surrounding environment. The simulation was based on pollutant gas dispersion calculated using Gaussian Plume equation. The research has involved climate secondary data on Cengkareng climatology Station for last 10 years. Besides, the primary data has also been taken in 7 point sampling locations to determine initial ambient air quality of existing 1 x 600 MW Coal Fired Power Plant. The data of existing 1 x 600 MW coal fired power plant has been taken from Adipala Steam Power Plant while the gas pollutant dispersion simulation has been done well using Gaussian Plume equation. The result showed that gas emission for NO2, and TSP parameter in all scenarios and SO2 gas parameter in several scenarios were exceeding the Threshold Limit Value. Thus, a technology is needed to minimize produced emission gas. The increase of gas pollutant in all sampling locations was not significantly increasing and those gas pollutants were not generally exceeding the Threshold Limit Value permitted by the government regulation.